Historic landscapes and mental well-being - Darvill, Timothy; Barrass, Kerry; Drysdale, Laura; Heaslip, Vanessa, 1974-; Staelens, Yvette (Archaeopress Publishing Ltd., 2019)
Using archaeological sites and historic landscapes to promote mental well-being represents one of the most significant advances in archaeological resource management for many years. Prompted by the Human Henge project (Stonehenge/Avebury World Heritage Site), this volume provides an overview of work going on across Britain and the near Continent.